The regulatory role of PTTG1 in proliferation and migration of thyroid cancer - Jianjun Wang; Chenjun Guo; Junyu Cao; Li Li (Discover Oncology)
Abstract Purpose To investigate the role of PTTG1 in thyroid cancer, focusing on its impact on proliferation, migration, and the regulation of p53-related signaling pathways. Methods We analyzed PTTG1 expression in thyroid cancer samples by using the TCGA database and validated our findings in tissue samples and cell lines. Functional assays including knockdown experiments using shRNA, CCK-8 assays for proliferation, scratch wound healing and Transwell assays for migration, and in vivo tumorigenesis experiments in mice were conducted. Expression levels of cell cycle markers (p27, p21, CDK1, p53) were assessed by qPCR and western blot. Results PTTG1 expression was significantly upregulated in thyroid cancer tissues and cells, correlating with reduced overall survival in patients. Knockdown of PTTG1 in thyroid cancer cells led to decreased proliferation and migration capabilities, as demonstrated by CCK-8 and clonogenic assays, scratch wound healing, Transwell assays, and reduced tumor growth in vivo. Mechanistically, PTTG1 downregulation resulted in increased expression of p53 and its downstream effectors, suggesting a role for PTTG1 in suppressing the p53-related signaling pathway. Conclusion Elevated PTTG1 expression promotes proliferation and migration of thyroid cancer cells and correlates with poor patient survival.